2004
DOI: 10.1021/ac0352023
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Volatile Aromatic Compounds Using a Compact Laser Ionization Detector with Fast Gas Chromatography

Abstract: We report results for a new gas chromatography detector that is comparatively sensitive and far more selective for aromatic compounds than the traditional photoionization detector. The detection means is multiphoton ionization at atmospheric pressure. The ionization source in these experiments is a diode-pumped passively Q-switched microchip laser operating at 266 nm. Experiments were conducted with the detector interfaced to a fast gas chromatograph. For <20 s elution time, limits of detection were <1 pg for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Please do not adjust margins Please do not adjust margins which is set in relation to the standard gas of 1 ppm. From 10 consecutive chromatograms, we obtain 2 ppb for toluene and 0.5 ppb for p-xylene, which is competitive with LODs from previously published fastGC setups with soft ionization mass spectrometry 9,17,18 or fast GC with sensor array detection 6 for analytes of similar volatility. It has been found that the photoionisation cross section at 126 nm of p-xylene differs by less than 25% of the one of toluene 19 , we attribute the lower LOD of p-xylene to the highe r trapping efficiency.…”
Section: Analytical Figures Of Meritmentioning
confidence: 66%
“…Please do not adjust margins Please do not adjust margins which is set in relation to the standard gas of 1 ppm. From 10 consecutive chromatograms, we obtain 2 ppb for toluene and 0.5 ppb for p-xylene, which is competitive with LODs from previously published fastGC setups with soft ionization mass spectrometry 9,17,18 or fast GC with sensor array detection 6 for analytes of similar volatility. It has been found that the photoionisation cross section at 126 nm of p-xylene differs by less than 25% of the one of toluene 19 , we attribute the lower LOD of p-xylene to the highe r trapping efficiency.…”
Section: Analytical Figures Of Meritmentioning
confidence: 66%